REACTION OF SHARE PRICES TO DIVIDEND POLICY OF NON-FINANCIAL FIRMS IN NIGERIA: A PANEL DATA APPROACH - A. Emeka-Nwokeji, Nkechi; Nangih, Efeeloo; O. Chiedu, Christian; N. Ekwunife, Ebele (Copernican Journal of Finance & Accounting, 2022)
The study analyzed how share prices react to dividend policies of non-financial firms in Nigeria. Data were collected from a sample of 31 non-financial firms using an ex post facto research design from 2013 to 2019, resulting in 217 firm-specific observations. Descriptive statistics, diagnostic tests, and inferential statistics were used as statistical tools of analysis. Results revealed that dividend per share positively and significantly affects share prices of sampled firms. This finding affirms Gordon’s bird in hand theory that share prices are affected by dividend. Dividend payout ratio, dividend yield, firm, size and firm age do not have significant effect on share prices of sampled firms. Consequently, the study recommends that firms should ensure that a good dividend policy is implemented and that dividend per share policies are maintained, as this has been empirically demonstrated to influence share prices.